(untitled) (Journal of Surgical Sciences, 2019)
Background: The role of axillary dissection as an effective means of controlling regionalnodal disease, has long been recognized. It is associated with significant complicationsand might be more selectively applied only to patients harboring micrometastases to thesentinel nodes. Objective: To assess the complications of level I and II axillary lymph node dissection inthe treatment of stage I and II breast cancer, with mastectomy. Methods: One hundred patients having total mastectomy with axillary dissection, wereevaluated for more than 1 year after surgery for arm swelling as well as non-edemacomplications. All patients had measurements of circumference of upper limb at 4 siteson both the operated and non operated sides. Results: No patient had an axillary recurrence, difference in circumference of upperlimb at the midbiceps level >2 cm - 13% (p <0.001), difference at the antecubitalfossa>12% (p < 0.001), at the mid forearm>2cm - 8% (p < 0.005), and at the wrist 4%(n.s.). Four patients (4%) had mild swelling of the hand. Seventy seven (77%) patientshad numbness or paresthesias of the medial arm and/or axilla after surgery; in 63(82%) of these, the problem had lessened or had resolved on follow-up assessment.Medical therapy with anti-tubercular drugs ranging from 9 to 12 months with follow upmonthly was the mainstay of treatment. Surgical intervention reserved for selectedrefractory cases. Extension of anti-tubercular therapy from 9 to 12 or 18 monthsrequired in fifty-eight(58) patients on the basis of slow clinical response. Completeresolution obtained in 92 patients but residual tiny mass in eight patients confirmed byrepeated FNAC to be fibrotic. Conclusion: Level I and II axillary dissection is associated with various complications.Sentinel lymphadenectomy may be proposed as an alternative to elective axillarydissection. Journal of Surgical Sciences (2017) Vol. 21 (1) :24-28